Transitive Phenomena in the Grammatical System of the Language - Natalia Scherbii (Journal of Vasyl Stefanyk Precarpathian National University)
The article deals with the complex issue of transitivity in the parts of the language system, their morphological and syntactic characteristics, and functional variability. It describes the preconditions for the conversion transition, and in particular the peculiar verbal character of the Ukrainian language. The article also characterizes certain typological variants of conversion, in particular, among the so-called hybrid parts of speech – adjectives, infinitives, verb-turned nouns, the grammatical properties of which border on several parts of the language. The hybrid parts of language reveal syncretism at the morphological and semantic-syntactic levels. Transitive phenomena in the parts of speech also include exclamations, in particular verbal sound-imitations which are subject to transformation into an onomatopoeic verb. The article drives to conclusion that transitive phenomena in language testify to profound internal changes in both the semantic structure and the form of the word, and consequently denote the development and changes in the language.